The Amazing History of Element Names - Avenas, Pierre (Hors Collection., 2020)
What is the connection between planet Mars and Iron Man, nickel and the Seven Dwarves, or DNA, walnuts and Jupiter, fuchsine, the fox and Zorro, or even ammoniac and the god Amun? This book tells the stories behind the naming of the elements, whether they are chemical elements of the Periodic Table, first published by Mendeleev in 1869, or organic elements which are components of DNA and RNA, as well as proteins, themselves elements of living kingdom, plants and animals. The book goes further, into materials and products which became essential elements of modern life. Readers will learn that the names often refer to (or reveal) dreams and aspirations of men and women of their time. This truly amazing history of the names guides us through an incredible set of worlds: nature, astronomy, history, literature, journeys, and even takes in contributions from legends and mythology.